Effect of foliar zinc application on growth and yield of rice (Oryza sativa) in the Indo-Gangetic Plains of India - RAHUL SAIKH; KANU MURMU; ARUP SARKAR; RAMYAJIT MONDAL; KALYAN JANA (Smujo International, 2022)
Abstract. Saikh R, Murmu K, Sarkar A, Mondal R, Jana K. 2022. Effect of foliar zinc application on growth and yield of rice (Oryza sativa) in the Indo-Gangetic Plains of India. Nusantara Bioscience 14: 182-187. A field experiment was conducted on rice cv. Satabdi (IET-4768) to investigate the effect of foliar zinc application at different stages during the post-Kharif season of 2019. The field experiment was carried out at 'C' block farm of (B.C.K.V), Kalyani, India, with eight different foliar 0.5% 0.5% ZnSO4 (ZnSO4) are T1: Control (without foliar application), T2: Foliar application of 0.5% ZnSO4 at Panicle Initiation, T3: Foliar application of 0.5% ZnSO4 at Booting, T4: Foliar application of 0.5% ZnSO4 at Panicle Initiation and 1 week after flowering, T5: Foliar application of 0.5% ZnSO4 at Panicle at 1 week after Flowering, T6: Foliar application of 0.5% ZnSO4 at Panicle at 2 weeks after flowering, T7: Foliar application of 0.5% ZnSO4 at Panicle at 1 week and 2 weeks after flowering and T8: Foliar application of 0.5% ZnSO4 at Panicle Initiation, Booting, 1 week and 2 weeks after flowering respectively in randomized complete block design with three replication. The result of the experiment revealed that rice plants treated with the combination of T4i.e. Foliar application of 0.5% ZnSO4 at Panicle Initiation and 1 week after flowering have resulted in the highest grain yield of 5.09 t/ha, which was 50.59% higher (3.38 t/ha) than the T1i.e. the control. Furthermore, residual nutrient status was also highest in the plot treated with T4i.e. Foliar application of 0.5% ZnSO4 at Panicle Initiation and 1 week after flowering.